The BlackBerry Pearl pocketguide : all the secrets of the BlackBerry Pearl, pocket sized - Farkas, Bart (Peachpit Press, 2006)
Everyone knows how addictive a BlackBerry can be--they don't call them "crackberries" for nothing! Well, you haven't seen anything until you try the brand new BlackBerry Pearl. This brand new phone has it all, and it's small, smart, and stylish too. Not only does it have all the features you expect from a BlackBerry (Phone, Email and Text Messaging, Instant Messaging, Organizer, Browser) but it has some great new "Wow" features including a camera, media player, and BlackBerry Maps. In The BlackBerry Pearl Pocket Guide, trusted gadget teacher and best-selling author Bart G. Farkas reveals the secrets to using this amazing new phone: learn how to take cool pictures and share them with your colleagues, view Web pages, import songs, manage your appointments, communicate with email, text and instant messaging, retrieve maps and detailed driving directions, and even import video. This handy pocket-sized guide also walks readers through the fun lifestyle functions, from playing a new Sudoku game every day to charting your diet and exercise patterns. In this low-priced guide, you'll find compact-yet-detailed coverage of everything the BlackBerry Pearl can do, as well as all the necessary information on "why" you should use it to be more productive.